TRADEMARK NAMING ETHICS AND ITS IMPLICATIONS FOR HALAL STATUS ACCORDING TO ISLAMIC LAW - Riskia Ulfa; Fakhrurrazi M Yunus (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This study comprehensively explores the issue of poorly chosen names that contain negative connotations for culinary products and their impact on the halal status of food. The primary focus is on a food stall named